Elimination of Thermally Generated Charge in Charged Coupled Devices Using Bayesian Estimator - Svihlik, Jan; Pata, Petr (Společnost pro radioelektronické inženýrství, 2008)
This paper deals with advanced methods for elimination of thermally generated charge in astronomical images, which were acquired by a Charged Coupled Device (CCD) sensor. There exist a number of light images acquired by telescope, which were not corrected by dark frame. The reason is simple: the dark frame doesn’t exist, because it was not acquired. This situation may for instance come when sufficient memory space is not available. Correction methods based on the modeling of the light and dark image in the wavelet domain will be discussed. As the model for the dark frame image and for the light image the generalized Laplacian was chosen. The model parameters were estimated using moment method, whereas an extensive measurement on an astronomical camera was proposed and done. This measurement simplifies estimation of the dark frame model parameters. Finally a set of astronomical testing images was corrected and then the objective criteria for an image quality evaluation based on the aperture photometry were applied.
Keywords: Dark frame correction; Bayesian estimator; discrete wavelet transform; generalized Laplacian